ChemInform Abstract: Recent Progress in Ferrofluids Research: Novel Applications of Magnetically Controllable and Tunable Fluids. Issue 28 (June 2016) - Torres‐Diaz, I.; Rinaldi, C.
Abstract: Review: 221 refs.